Keadilan Distribusi Ekonomi pada Masa Khalifah Umar Bin Khattab: Refleksi atas Ketimpangan Ekonomi di Indonesia - Lina Trisnawati; Nila Nafisatul Bashiroh; Muhamad Aqim Adlan; Mochamad Arif Faizin (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study explores the concept of distributive justice during the era of Caliph Umar ibn al-Khattab and examines its relevance to current economic inequality in Indonesia. The urgency of this topic arises from Indonesia’s persistent income disparities, as reflected in fluctuating but relatively high Gini ratios in recent years. The research aims to analyze how Umar’s fiscal principles, rooted in fairness, accountability, and social welfare, can offer meaningful insights for improving contemporary economic distribution. Using a qualitative approach through library research, the study reviews classical Islamic sources, historical records, and recent statistical data. The findings indicate that Umar’s economic governance, particularly the management of the Bayt al-Mal, equitable taxation, and systematic allocation of public resources, reflects a model of distributive justice that prioritizes social balance and public welfare. When compared with Indonesia’s inequality trends, these principles provide relevant reference points, especially regarding transparent fiscal management, strengthened welfare mechanisms, and productive public expenditure. The study concludes that Umar’s values can inspire policy directions aimed at reducing economic disparities and enhancing inclusive development in Indonesia.